Location Selection Using the Analytic Hierarchy Process: A case study of private vehicle inspection centers, Mueang, Songkhla - Sukkrajang, Kantamon; Rattanakool, Tanarat (Academic Journal of Industrial Technology Innovation, 2024)
This study employed the Analytic Hierarchy Process (AHP) to examine the location selection process for private vehicle inspection centers (PVICs). The research aims to (1) identify factors influencing location selection, (2) assess the relative importance of these factors, and (3) evaluate decision consistency. Data were collected through interviews with executives or decision-makers from seven PVICs in Mueang District, Songkhla Province, Thailand. An interview instrument was developed based on a comprehensive literature review of location selection research. The findings reveal four primary factors affecting the PVIC location selection, ranked in descending order of importance: facilities, customer base, raw material sources, and business premises details. Within these categories, land price, reduction of raw material transportation costs, product sales, and transportation convenience emerged as the most critical sub-factors, respectively. The analysis confirms decision consistency across all factors, with the Consistency Ratio (CR) below 0.10.